Development of Multiplechoice Test Instruments to Improve Scientific Literacy in Madrasah Aliyah (MA) - Sudirman; Rusilowati , Ani; Susilaningsih, Endang (International Journal of Scientific Research and Management (IJSRM), 2024)
The ability to analyze and interpret scientific information is very important in the era of advanced technology. For Madrasah Aliyah (MA) students, scientific literacy is crucial for academic and future achievements, including understanding scientific concepts, interpreting data, making decisions, and communicating scientific ideas. Although scientific literacy is important, many MA students face challenges due to traditional teaching methods and inappropriate assessment. This research aims to develop and measure a multiplechoice test instrument for MA students' scientific literacy, empirically validated to improve science education and prepare students to face the modern world. Research and development (research and development) with 3D models (Define, Design, Development). Focus on scientific literacy questions with PISA indicators. Overall, it shows that the instruments used are very good and valid, and provide a positive picture of students' scientific literacy abilities, although there are still certain areas that need to be improved. Questions with poor power differences need to be repaired or replaced, and questions with sufficient power differences need to be revised. Low scores in explaining scientific phenomena require additional guidance. Regular monitoring and revision is important to maintain the quality of the instrument. This instrument is valid and reliable, but continuous improvement is needed.